Flat Oral Glucose Tolerance Test during Pregnancy and Risk for Type 2 Diabetes: A 5-Year Cohort Study - Tarashandegan, Danit; Naeh, Amir; Hallak, Mordechai; Toledano, Yoel; Gabbay-Benziv, Rinat; Maor-Sagie, Esther (American Journal of Perinatology, 2024)
This study aimed to evaluate the risk of type 2 diabetes mellitus (T2DM) in women with flat response in the 100-g oral glucose tolerance test (OGTT) performed during pregnancy in a large cohort of women with up to 5 years of follow-up.A retrospective analysis of women with documented OGTT during pregnancy and T2DM data up to 5 years after pregnancy. Gestational diabetes mellitus (GDM) screening was done by a two-step strategy. Glucose levels during pregnancy were extracted from the computerized laboratory system of Meuhedet Health Maintenance Organization (HMO) and cross-tabulated with the Israeli National Diabetes Registry. Flat OGTT was defined as fasting glucose <95 mg/dL and three postprandial values lower than 100 mg/dL. The cohort was stratified by OGTT results to normal glucose values, flat OGTT, and GDM according to Carpenter and Coustan thresholds. Cumulative risk for T2DM was evaluated and compared between groups. Statistical analysis included univariate analysis followed by survival analysis.A total of 14,122 parturients entered the analysis. Of them, 965 (6.8%) had flat OGTT, 11,427 (80.9%) had normal OGTT, and 1,730 (12.3%) had GDM. Women with flat OGTT were younger, had lower body mass index (BMI; kg/m2), and had lower rates of hypertension. Their glucose values throughout pregnancy were lower compared with the other groups (p < 0.001 for all). During the study period and following adjustment to maternal age, obesity, and hypertension, women with flat OGTT had a low incidence of T2DM, even when compared with women with normal OGTT (adjusted hazard ratio 0.212, 95% confidence interval 0.052–0.856).Parturients with flat OGTT during pregnancy are at a low risk of developing T2DM up to 5 years following pregnancy.
Keywords: diabetes mellitus; gestational diabetes; pregnancy; oral glucose tolerance test; flat OGTT